Effect of exogenous emulsifier and different fat sources on the performance, carcass characteristics, nutrient digestibility, and serum lipid profile of broiler chickens - Tavares, Fernando Barbosa; Lima, Kedson Raul de Souza; Manno, Maria Cristina; Barata, Yan Matheus Leary; Pinheiro, Higor César de Oliveira; Arruda, Janaína de Cássia Braga; Faturi, Cristian (Brazilian Journal of Veterinary Research and Animal Science, 2022)
A study was conducted to evaluate the effect of an emulsifier on reduced-energy diets using two fat sources for broilers. The study was designed as a 2 x 3 factorial arrangement of treatments. The first factor was 2 fat sources (poultry fat or beef tallow). The second factor was a basal diet with the recommended energy levels, a diet with a 0.83 MJ/kg of energy reduction, and a diet with an energy reduction and inclusion of 1 g emulsifier/kg of diet. The emulsifier used in this study was composed of soy lecithin and polyethylene glycol ricinoleate. The emulsifier increased apparent metabolizable energy (AME) and apparent metabolizable energy corrected for nitrogen balance (AMEn) in beef tallow diets compared to energy-reduced diets (P<0.001). Broilers fed poultry fat had higher weights and weight gains at 35 and 42 d of age (p=0.001), and they had higher daily deposition of fat in the carcass (P = 0.025) when compared to diets with beef tallow. The inclusion of emulsifiers in broiler diets improves AME and AMEn but did not affect the energy reduction diets, whichresulted in reduced performance, decreasing daily fat deposition, but without effects on serum lipid profile in broilers.